The oxygen uptake efficiency slope does not accurately predict V˙O2peak of children – the Arkansas Active Kids study - Edwards, Timothy; Børsheim, Elisabet; Weber, Judith L.; Diaz, Eva C. (Frontiers in Physiology, 2024)
Background: Cardiorespiratory fitness (CRF) is a vital indicator of health. However, accurately measuring peak oxygen consumption (V ̇O2peak) to determine CRF in children can be challenging.The oxygen uptake efficiency slope (OUES) has been proposed as an alternative metric for predicting V ̇O2peak in children, but its accuracy and agreement with measured V ̇O2peak remain unclear.Methods: A secondary analysis was conducted in 94 children (ages 7-10 years) who completed an incremental cycle ergometer test to measure V ̇O2peak. Body composition (Dual-energy X-ray absorptiometry) was measured, and fat mass index (FMI, kg/m 2 ) and fat-free mass index (FFMI, kg/m 2 ) were calculated. OUES was determined using all respiratory data (OUES100%) collected during the cycle ergometer test and using data only up to 60% of heart rate reserve (OUES60%HRR).Regression equations to predict V ̇O2 peak (Pred-V ̇O2 peak) were derived from simple and multiple linear regression analysis. Bland-Altman analysis assessed the level of agreement between Pred-V ̇O2 peak and measured V ̇O2peak.Results: OUES60%HRR (β = 0.46, p <0.0001), age (β = 56.0, p = 0.0004), White race (β = 173.3, p <0.0003), FFMI (β = 0.98.6, p <0.000), and FMI (β = -0.40.8, p <0.000) were retained in the final model. The difference between measured V ̇O2peak and Pred-V ̇O2 peak was not different from zero (p = 0.999). There was a positive association between the difference of measured V ̇O2peak and Pred-V ̇O2 peak and the average of the two methods (β = 0.79, p = 0.0028).There was no mean bias between measured V ̇O2peak and Pred-V ̇O2 peak. However, magnitude bias was present even after considering other significant predictors of V ̇O2peak (FMI, FFMI, race, and age) in the regression equation. Caution is advised when using OUES to predict V ̇O2peak in children.